2017
DOI: 10.1088/1748-605x/aa9bbc
|View full text |Cite
|
Sign up to set email alerts
|

Porosity effect of 3D-printed polycaprolactone membranes on calvarial defect model for guided bone regeneration

Abstract: The appropriate porosity and pore size of barrier membranes were associated with the transportation of biomolecules required for new bone formation and angiogenesis. In this study, we fabricated three-dimensional (3D)-printed resorbable polycaprolactone (PCL) membranes with different porosities (30%, 50%, and 70%) to evaluate the effective pore size for guided bone regeneration (GBR) membranes. To analyze mechanical properties and cytocompatibility, PCL membranes prepared using extrusion-based 3D printing tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 51 publications
1
37
0
Order By: Relevance
“…The scaffold porosity is an important factor affecting the performance of scaffolds. Shim [ 71 ] found that 3D printed PCL GBR membranes with 30% porosity (130 μm pore size) were excellent for calvarial regeneration. Second, the pore structure has also been studied.…”
Section: Pcl-based Composite 3d Scaffoldsmentioning
confidence: 99%
“…The scaffold porosity is an important factor affecting the performance of scaffolds. Shim [ 71 ] found that 3D printed PCL GBR membranes with 30% porosity (130 μm pore size) were excellent for calvarial regeneration. Second, the pore structure has also been studied.…”
Section: Pcl-based Composite 3d Scaffoldsmentioning
confidence: 99%
“…Skull injury repair has primarily been investigated in small animal models such as rats [26][27][28][29] and rabbits. [30][31][32] These studies have made important contributions to the development of strategies for calvarial bone regeneration. However, rodent calvaria are very different from that of humans, and a large animal CSD model is ultimately necessary for enabling clinical translation.…”
Section: Discussionmentioning
confidence: 99%
“…A synthetic bioresorbable membrane using a combination of polycarprolactone (PCL) and beta tricalcium phosphate (β-TCP) has recently been introduced to overcome the drawbacks of existing membranes [13]. The PCL/β-TCP membrane showed increased mechanical stability and slower degradation compared to conventional collagen membranes with reliable bone regeneration [14].…”
Section: Introductionmentioning
confidence: 99%
“…Since the PCL/β-TCP membrane is fabricated with 3D printing techniques, the membrane can be designed and printed as an individually tailored membrane, which fits to each bone defect [13]. Acquiring a perfect fit around a bone defect can result in reduced surgery time as well as the prevention of membrane exposure [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation